Analysis of Sidoarjo Health Office Instagram Content as a Covid-19 Information Media: Analysis Content Instagram Dinkes Sidoarjo Sebagai Media Informasi Covid-19 - Andiarti, Nabila Ayu; Aesthetika, Nur Magfirah (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the semantic content analysis on Instagram @dinkes_sidoarjo as a medium of information on covid-19 for the people of Sidoarjo in August 2021. The research is based on the popular social media, namely Instagram. regarding covid-19. This makes the post and caption on Instagram @dinkes_sidoarjo whether it has become a medium of information for the people of Sidoarjo. This research method uses qualitative and data collection in the form of documentation as many as 18 posts. This data analysis uses semantic content analysis, which is analyzed by designation, characterization, and statement analysis. The results show that @dinkes_sidoarjo is more directing the reader and is more about discussing the map of the spread of covid-19 in an area which was repeated 132 times in August 2021. This can be interpreted that as a medium of information @dinkes_sidoarjo in his post does not discuss covid-19 education and Covid-19 vaccination activities as an effort to reduce the risk of transmission in August 2021